The influence of acetylation status of tuberculosis patients on the isoniazid serum concentrations and sputum conversion after intensive phase therapy - Dwi Indria Anggraini; Erna Kristin; iwan Dwiprahasto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Isoniazid (INH), one of the major antituberculosis drugs, is metabolized by acetylation. Previously study proved the significant differences of serum INH concentration between subject with fast and slow acetylation status. However, the correlation of acetylation status with treatment outcome after fixed-dose combination antituberculosis therapy (FDC-ATT) was not explained. The aim of this study was to evaluate the influence of acetylation status on the treatment outcome and the serum INH concentrations in the adult tuberculosis patients underwent FDC-ATT. A cross sectional study was carried out on 31 tuberculosis patients. Acetylation status was measured by spectrophotometer and serum INH concentration was measured by high performance liquid chromatography (HPLC). Sputum conversion assay was conducted by Ziehl Nelsen method. t-Test, chi square, Mann-Whitney, and Fisherman were used to analyze the data. The proportion of the fast acetylator was 61.3%, whereas the slow acetylator was 38.7%. The proportion of success and failure sputum conversion were 83.9% and 16.1%, respectively. The mean serum INH concentration in the fast acetylator groups (1.52 ± 0.15 μg/mL) was significantly lower than that in the slow acetylator groups (3.84 ± 0.35 μg/mL). The failure conversion risk of the fast acetylator group was about two folds higher than the slow acetylator group, although it was not significantly different (RR=2.53; 95% CI=0.32-20.00; p>0.05). Moreover, the mean serum INH concentration in success (2.46 ± 0.31 μg/mL) and failure (1.89 ± 0.20 μg/mL) sputum conversion was not significantly different (p>0.05). In conclusion, the acetylation status does not influence the sputum conversion in adult tuberculosis patients after FDC-ATT although the serum INH concentration on slow acetylation status is higher than that fast acetylation status.